Trypanosoma brucei Lipophosphoglycan Activates Host Immune Responses via the TLR-mediated p38 MAP Kinase and NF-κB Pathways - Kai Zhang; Ning Jiang; Naiwen Zhang; Liying Yu; Xiaoyu Sang; Ying Feng; Ran Chen; Qijun Chen (Zoonoses, 2023)
This study was aimed at investigating the immunoregulatory effects of trypanosomal lipophosphoglycan (LPG) anchored to trypanosome membranes, including the formation of neutrophil extracellular traps (NETs) and neutrophil cytokine release after parasite infection. The interaction of cell surface TLR receptors with LPG, which signals cellular responses during Trypanosma brucei infection, was systematically investigated. The cytokine expression profile in neutrophils after exposure to T. brucei LPG, and the involvement of TLR2, TLR4, p38 MAP kinase, and NF-κB in NET formation were studied with molecular immunological approaches including quantitative PCR, western blotting and immunofluorescence. T. brucei -derived LPG induced phosphorylation of p38 MAP kinase and NF-κB, thereby stimulating neutrophil secretion of IL-1β, IL-8, and TNF-α. The blockade of Toll-like receptor 2/4 and specific inhibitors of MyD88, p38 MAP kinase, and NF-κB decreased cytokine release and the phosphorylation of both kinases. Furthermore, the exposure of neutrophils containing LPG to IL-1β and LPG-induced cell supernatants promoted the release of NETs. Our findings suggest that T. brucei LPG activates neutrophil IL-1β secretion via the TLR-mediated p38 MAP kinase and NF-κB pathways, thereby promoting the formation of LPG-stimulated NETs.